The Impact of Using Three Methods to Present Scientific Concepts on Developing Creative Thinking Skills: A Semi Empirical Study on a Sample of Kindergarteners at 5-6 Years Old in Lattakia (Journal of Hama University, 2024)
This research aimed to investigate the impact of using three styles of inductive deductive method of teaching scientific concepts on developing creative thinking skills (Fluency, Originality, and Imagination) for a sample of kindergarten children consisting of (48) boys and girls, distributed into three experimental groups.The researcher applied the style of: positive examples - definition - positive examples to the first group, and applied the style of: positive examples - definition - positive examples - negative examples to the second group. Meanwhile, the third group was subjected to the style of: positive examples - definition - negative examples - positive examples.The researcher used the Torrance Test of Creative Thinking in Action and Movement, then collected, analyzed, and statistically processed the data using the SPSS program at a significance level of (0.05). The results showed the following: 1- The big positive impact of using the three styles of teaching scientific concepts on the development of creative thinking skills for members of the research sample, both sub- and totally.2- The second and third styles outperformed the first style on the development of creative thinking skills for members of the research sample, both sub- and totally.3- The impact of using the second and third styles on the development of creative thinking skills for members of the research sample of the research sample is similar, sub- and totally.Based on the research results, the researcher provided some suggestions.
Keywords: Impact; Scientific Concepts; Creative Thinking; Kindergarten Children